Localization of YAP activity in developing skeletal rudiments is responsive to mechanical stimulation - Murphy, Paula; Rolfe, Rebecca (University of Edinburgh (datashare), 2020)
Background: Normal skeletal development, in particular ossification, joint formation and shape features of condyles, depends on appropriate mechanical input from embryonic movement but it is unknown how such physical stimuli are transduced to alter gene regulation. Hippo/YAP signaling has been shown to respond to the physical environment of the cell and here we specifically investigate the YAP effector of the pathway as a potential mechano‐responsive mediator in the developing limb skeleton. Results: We show spatial localization of YAP protein and of pathway target gene expression within developing skeletal rudiments where predicted biophysical stimuli patterns and shape are affected in immobilization models, coincident with the period of sensitivity to movement, but not coincident with the expression of the Hippo receptor Fat4. Furthermore, we show that under reduced mechanical stimulation, in immobile, muscle‐less mouse embryos, this spatial localization is lost. In culture blocking YAP reduces chondrogenesis but the effect differs depending on the timing and/or level of YAP reduction. Conclusions: These findings implicate YAP signaling, independent of Fat4, in the transduction of mechanical signals during key stages of skeletal patterning in the developing limb, in particular endochondral ossification and shape emergence, as well as patterning of tissues at the developing synovial joint
Roles of Skeletal Muscle in Organ Development
PUBLISHED
Keywords: Skeletal development; Morphogenesis; Chondrogenesis; Mechanical regulation; Menchanosensory; Hippo; YAP; Genes & Society; Developmental Biology